Efecto de la temperatura y la humedad relativa en los parámetros productivos y la transferencia de calor en pollos de engorde (2007)
ABSTRACT: To achieve maximum productive yields in broiler production, it is indispensable to manage an appropriate environment that provides to the birds the good environmental conditions. In this work the effect of temperature and relative humidity in the productive performance and transfer of heat in broilers was evaluated, with the purpose of establishing the thermal comfort zone in the microclimate of Vegas de la Clara farm (Nordeste antioqueño, Colombia), to optimize the production models. In the first part of the work, the behaviour of breed Ross chickens in the breeding stage was determined by means of an exploratory descriptive statistical analysis, measuring changes of corporal temperature from birth (heterothermos with (corporal temperature of 39.741 ± 0.44 °C), until the chickens reached the endothermos), until the chickens reached the endothermos condition (corporal temperature of 40.37 ± 0.221 °C); when concluding this stage the homogeneity of the lot was determined, concerning body weight, with the purpose of obtaining uniformity in the experimental units (chickens) to carry out the experimental phase corresponding to the final stage of the productive period. In the experimental phase, the influence of three different temperatures (19, 25 and 31 °C) with a constant relative humidity of 75% on heat transfer and broiler productive yield as measured by food consumption, body weight, nutritional conversion and morbi-mortality, was evaluated. The results were evaluated by MANOVA with canonical contrasts and a totally randomized design of structures. The best productive behaviour to body weight and nutritional conversion was obtained at a temperature of 19 °C when compared to the other treatments (p < 0.05). Heat losses were represented in a psychrometric cart, which indicated that treatment at 19 °C, followed by treatments at 31 and 25 °C (p < 0.05), represented the greatest losses of sensible heat, respectively. Regarding latent heat losses statistically significant differences Regarding latent heat losses statistically significant differences were no found (p > 0.05).